1989
DOI: 10.1152/ajpregu.1989.256.4.r939
|View full text |Cite
|
Sign up to set email alerts
|

Body weight of rats following area postrema ablation: effect of early force-feeding

Abstract: This study examined the effect of intragastric force-feeding of a milk diet on body weights of rats with lesions of the area postrema/caudal medial nucleus of the solitary tract (AP/cmNTS). Force-feeding was conducted over the first 10 days after the ablation. Body weight was monitored both during and after force-feeding. Food intake was measured during all ad libitum feeding periods. During force-feeding, rats with AP/cmNTS lesions gained weight at the same rate as force-fed sham-lesioned rats or sham-lesione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…We do not dispose of enough evidence to say that exaggerated satiation is responsible for weight loss after brain lesion in humans. Nonetheless, it was repeatedly observed that experimental lesions of viscerosensory relays in non-obese rats including, most notably, the parabrachial and dorsovagal complexes can result in sustained weight loss with depressed ingestive behaviors (Hill and Almli, 1983;Hyde and Miselis, 1983;Kott et al, 1984;Kenney et al, 1989;Dayawansa et al, 2011). In agreement with the hypothesis presented in this article, the aforementioned observations strongly support the idea that derangements in the integrity of key brain sites involved in GI viscerosensory processing can cause weight loss with reduced food intake.…”
Section: Weight Loss and Brain Lesionssupporting
confidence: 88%
“…We do not dispose of enough evidence to say that exaggerated satiation is responsible for weight loss after brain lesion in humans. Nonetheless, it was repeatedly observed that experimental lesions of viscerosensory relays in non-obese rats including, most notably, the parabrachial and dorsovagal complexes can result in sustained weight loss with depressed ingestive behaviors (Hill and Almli, 1983;Hyde and Miselis, 1983;Kott et al, 1984;Kenney et al, 1989;Dayawansa et al, 2011). In agreement with the hypothesis presented in this article, the aforementioned observations strongly support the idea that derangements in the integrity of key brain sites involved in GI viscerosensory processing can cause weight loss with reduced food intake.…”
Section: Weight Loss and Brain Lesionssupporting
confidence: 88%
“…The AP has been related to several functions, such as vomiting (Borison, 1974) and food preference . Our results suggest that the development function of the AP must be basic; e.g., regulation of the body weight and fat Kenney et al, 1989). In this context, it is interesting to note that the proportionally biggest step in the development of body weight takes place between the third and fourth gestational months, when body weight increases from 20 g to 120 g (Hamilton, 1945), concurrently with the early maturation of the AP.…”
Section: Discussionmentioning
confidence: 69%
“…The afferent projections of the AP have been described as components of the vagus and glossopharyngeal nerves (see Miselis et al, 1987), whereas its efferent connections reach the nucleus of the tractus solitarius and the parabrachial nucleus (Lanca and Van der Kooy, 1985;Leslie and Gwyn, 1984;Strain et al, 1990). The AP and adjacent caudal-medial portion of the nucleus of the tractus solitarius are involved in the nausea and vomiting syndrome as well as in regulation of body weight (Borison, 1974;Borison et al, 1981;Gotow and Hashimoto, 1979;Kott et al, 1984;Bernstein et al, 1985;Kenney et al, 1989). The functions of the AP are also related to the effect of angiotensin I1 (Rabin et al, 1986;Barnes and Ferraro, 1984) and vasopressin in cardiovascular regulation (Michelini et al, 1986).…”
mentioning
confidence: 99%
“…Many studies examining the effect of AP lesions on body weight have shown clear decreases that are often maintained for weeks following such lesions (in which AP has been lesioned have provided somewhat contentious data, with some showing clear decreases in body weight following such lesions). [37][38][39] The effects of SFO lesions on food intake and body weight have not been extensively examined, although the predominant evidence suggests no profound effects of such lesions on these parameters. We have recently undertaken studies in which we have systematically lesioned SFO, AP or both CVOs concurrently, and although no clear effects of either single AP or SFO lesions on body weight and food intake have been shown, we have observed a reduction in body weight and food intake in animals in which both of these CVOs are lesioned (ED Baraboï et al, unpublished observations).…”
Section: The Circumventricular Organsmentioning
confidence: 99%